Pengaruh Promosi Penjualan, Kualitas Produk, Harga dan Daya Saing Perusahaan Terhadap Penjualan Produk PT. Gudang Garam, Tbk pada Area Penjualan Kota Padang - Fikriando, Eko; Ramadhi, Ramadhi; Relifra, Relifra (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
This research aims to determine the extent of the analysis regarding the influence of sales promotions, product quality and price on company competitiveness and its impact on product sales (case study analysis at PT. Gudang Garam, Tbk). This research consists of four independent variables, namely sales promotion, product quality, price and competitiveness and one product sales variable as the dependent variable. Sampling in this research used purposive sampling in which a sample of 100 respondents was obtained. Multiple linear regression analysis method, t-test, F-test and determination test. Based on the research results, it was found that: a) there is a positive and significant influence of sales promotion on product sales, b) there is a positive and significant influence of product quality on product sales, c) there is no significant influence of price on product sales, d) there is a positive and significant influence of competitiveness on product sales, e) there is an influence of sales promotion, product quality, price and competitiveness on product sales